Ketergantungan Mobilitas pada Temperatur Pengukuran Lapisan Porphyrin Alam: Elly Fatmawati, Utari, Budi Purnama, Kamsul Abraha - Elly Fatmawati, Elly Fatmawati; Utari, Utari; Budi Purnama, Budi Purnama; Kamsul Abraha, Kamsul Abraha (Jurnal Fisika dan Aplikasinya, 2025)
The effect of temperature on the mobility of thin films of natural porphyrin produced by the method of spin-coating deposition on the substrate Cu were discussed. Analysis of charge carrier were calculated using I-V measurements from temperature T = 200 C to 230 C. The experimental results show that the effect of thermal agitation increases the current. Mobility linearly increases with the increased of temperature. Finally, the response to the temperature rise in the value of the mobility of the sample with N = 14 much faster than N = 8.